Fractures of the Hallux in Children. (January 2015) - Petnehazy, Thomas; Schalamon, Johannes; Hartwig, Charlotte; Eberl, Robert; Kraus, Tanja; Till, Holger; Singer, Georg
Background: Foot fractures account for 5% to 13% of pediatric fractures. Fractures of the hallux require special attention due to its role in weight bearing, balance, and pedal motion. In this study, a large series of children with hallux fractures is presented. Methods: All children treated with fractures of the hallux between June 2004 and December 2011 were included. The medical records were analyzed and X-rays were reviewed. The fractures were classified according to their anatomic location and the type of fracture. Three hundred seventeen patients (mean age = 11.7 years; range, 1-18 years; 65% male) sustained a fracture of the hallux. Results: Most accidents (28%) occurred at sports facilities, and soccer was the most common cause of a fracture of the hallux (28%). Closed injuries were diagnosed in 92% of the patients; 8% of the children presented with open fractures. In 144 children, the growth plate was affected. Fifty-nine patients presented with diaphyseal fractures, 42 patients with osseous avulsions, and 40 patients with fractures of the distal part of the phalanx. Nineteen children had incomplete and 13 patients comminuted fractures. The vast majority of the children (86%) were treated conservatively. Operative interventions were required in 14% of the patients. Good outcome was achieved in both conservatively and operatively treated patients. Conclusion: In children, fractures of the hallux were most often caused by ball sports and had a good prognosis. The vast majority of these fractures could be treated conservatively yielding good outcome. Level of Evidence: Level IV, case series.